2009
DOI: 10.1093/annonc/mdp235
|View full text |Cite
|
Sign up to set email alerts
|

Early and short-term acenocumarine or dalteparin for the prevention of central vein catheter-related thrombosis in cancer patients: a randomized controlled study based on serial venographies

Abstract: In this study of early and short-term prophylaxis, acenocumarine was more effective than dalteparin on non-occlusive and asymptomatic CVCrT events. The first days following CVC insertion represent the highest risk for CVCrT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 25 publications
1
56
0
2
Order By: Relevance
“…5 Contrast venography in 114 patients 1 week after placement of a CVC detected DVT in 53%, but only 3% were occlusive. 6 Over the past 2 decades, although the use of CVCs has increased dramatically, the risk of CRTs per catheter has decreased, perhaps related to less thrombogenic catheters and improved insertion techniques. 7,8 Although the majority of asymptomatic CRT cases remain subclinical, symptomatic DVT occurs in 1%-5% of patients with a CVC (Table 1).…”
Section: Incidence Of Crtmentioning
confidence: 99%
“…5 Contrast venography in 114 patients 1 week after placement of a CVC detected DVT in 53%, but only 3% were occlusive. 6 Over the past 2 decades, although the use of CVCs has increased dramatically, the risk of CRTs per catheter has decreased, perhaps related to less thrombogenic catheters and improved insertion techniques. 7,8 Although the majority of asymptomatic CRT cases remain subclinical, symptomatic DVT occurs in 1%-5% of patients with a CVC (Table 1).…”
Section: Incidence Of Crtmentioning
confidence: 99%
“…Fixeddose warfarin did not reduce the incidence of symptomatic radiographically confirmed catheter-associated thrombosis compared with no treatment (7% vs. 6%; P = 0.98), but dose-adjusted warfarin did significantly reduce the incidence of symptomatic catheter-associated thrombosis (2.7% vs. 7.2%; RR, 0.38; P = 0.002) at the expense of increased major bleeding complications (3.4% vs. 1.5%; P = 0.04). Although one early study suggested efficacy with fixed-dose warfarin [16], other randomized trials [16][17][18] and meta-analyses [19,20] have failed to show a significant reduction in the incidence of symptomatic catheter-associated thrombosis with warfarin prophylaxis.…”
Section: Pharmacologic Prevention Of Catheter-associated Thrombosis Imentioning
confidence: 99%
“…Similarly, several randomized studies explored the efficacy of prophylactic-dose low-molecular-weight heparin [17,21,22]. In one trial, 385 cancer patients were randomized to enoxaparin (40 mg daily) or placebo, and venography was performed 6 weeks later to determine the primary endpoint of asymptomatic upper extremity DVT [22].…”
Section: Pharmacologic Prevention Of Catheter-associated Thrombosis Imentioning
confidence: 99%
“…The efficacy and safety of using anticoagulant prophylaxis to prevent CRT have been investigated in a number of randomized trials (Table 3) [10][11][12][38][39][40][41][42][43][44][45]. The earliest studies suggested that low-dose warfarin (1 mg daily) or LMWH at a standard postoperative prophylaxis dose could significantly reduce the incidence of CRT in cancer patients [38,43].…”
Section: Prevention Of Crtmentioning
confidence: 99%